Análisis del Impuesto a la Renta del Régimen RIMPE Emprendedor y su Incidencia en la Recaudación Tributaria en la Ciudad de Loja periodo 2021-2022 - Medina Guamán, Bety Elizabeth (2023)
The main objective of the research work was to analyze the Income Tax of the entrepreneurial RIMPE Regime and its incidence on the Tax Collection in the city of Loja, period 2021-2022, for this reason it was carried out as a pre-requirement to obtain the degree of Master in Accounting and Finance, developed according to the Academic Regulations of the National University of Loja. The research has a mixed approach, combining qualitative and quantitative methods. In the qualitative aspect, an analysis was carried out to compare the tax regulations of the simplified regimes in Ecuador. On the other hand, in the quantitative approach, information was obtained from the Internal Revenue Service database and the statistics related to the income tax of the RIMPE regime collected during the period 2021-2022 were analyzed. In this way, we sought to obtain a comprehensive and accurate view of the impact on the tax regime and tax collection during the period analyzed in compliance with the objectives. The type of research used was exploratory and descriptive. In the exploratory approach, information was sought for the theoretical framework and secondary data from the Internal Revenue Service and previous studies were collected to interpret the reality of income tax collections in the entrepreneurial RIMPE regime in the city of Loja. Regarding the descriptive approach, specific information was collected on the collections of the entrepreneurial RIMPE regime in the year 2021-2022, evaluating its impact. Finally, the work under investigation provided some specific conclusions and recommendations that were a reference for the income tax, with the objective of guaranteeing an adequate taxation system in Ecuador that allows collecting what is necessary, this was done through clear rules and responding to the ability of each taxable person to contribute without any discrimination.